KERAGAMAN GENETIK POPULASI Calophyllum inophyllum MENGGUNAKAN PENANDA RAPD (RANDOM AMPLIFICATION POLYMORPHISM DNA) - ILG Nurtjahjaningsih; Titin Haryanti; AYPBC Widyatmoko; Sapto Indrioko; Anto Rimbawanto (Jurnal Pemuliaan Tanaman Hutan, 2015)
The aims of this study were to assess genetic diversity within populations and genetic relationship among populations of C. inophyllum. Leaf samples as template DNA were collected from 10 natural populations and 1 plantation. Five random amplified polymorphism DNA (RAPD) markers consisted 30 loci were conducted to genetic analysis. Results showed genetic diversity within populations were in low to moderate level (mean HE=0.186). There is no private allele in any populations. The analysis of molecular variance (AMOVA) showed that genetic differentiation among Islands was insignificant; but the differentiation was siginificant among populations and individual trees. Genetic distance among populations was in low to moderate level (mean Da=0.250). Cluster analysis clearly divided the 11 populations into 2 clusters; cluster I consisted Selayar, Lombok, Gunung Kidul and Padang populations; cluster II consisted Way Kambas, Madura, Ketapang, Dompu, and Yapen populations. The genetic relationships did not associate with their geographical locations. In conclusion, genetic diversity and genetic relationship among populations of C. inophyllum was in moderate level.